The Last of the Cheju Divers - Rob Waring (Boston, United States Cengage Learning, Inc, 2007)
Cheju, South Korea, is known for its traditional women divers. They have long dived into the ocean to look for seafood. It's dangerous, but there were no other jobs available. Now, women in Cheju have more choices. What jobs can they do? What will happen to the Cheju divers?
Keywords: Read Aloud Non Fiction